Analisis Strategi Manajemen Guru dalam Meningkatkan Kualitas SDM Siswa Sangkhom Islam Wittaya School - Della Puan Salsabillah; Syahrul Amsari (Jurnal Dirosah Islamiyah, 2024)
Improving the quality of Human Resources (HR) among students is a primary goal of education. Teachers play a crucial role in achieving this objective. Effective teacher management strategies can help enhance students' HR quality. This study aims to analyze teacher management strategies in improving students' HR quality at Sangkhom Islam Wittaya School. Conducted using qualitative methods, the research utilized interview, observation, and documentation techniques for data collection. Findings revealed that the teacher management strategies at Sangkhom Islam Wittaya School encompass enhancing teacher competencies, professionalism, motivation, well-being, as well as learning facilities and infrastructure. These strategies have proven effective in enhancing students' HR quality, including improved academic and non-academic performance and character development. The research suggests recommendations such as integrating teacher competencies, reinforcing professionalism, boosting teacher motivation and well-being, improving learning facilities, employing innovative teaching methods, and continuous evaluation.